Design, synthesis, and evaluation of competitive inhibitors of Trypanosoma cruzi Ribose 5-Phosphate Isomerase type B - Gonzalez, Soledad Natalia (2021)
Ribose 5-phosphate isomerase type B (RPI-B) is a key enzyme of the pentose phosphate pathway that catalyzes the isomerization of R5P and Ru5P. Trypanosoma cruzi RPI-B (TcRPI-B) appears to be a suitable drug-target mainly due to: (i) its essentiality (as previously shown in other trypanosomatids), (ii) it does not present a homologue in mammalian genomes sequenced thus far, and (iii) it participates in the production of NADPH and nucleotide/nucleic acid synthesis that are critical for parasite cell survival.